2021
DOI: 10.1021/acs.nanolett.1c00273
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Domain Wall Engineered Spin-Triplet Josephson Junctions and SQUID

Abstract: Spin-singlet Cooper pairs convert to spin-triplet Cooper pairs on passing through a magnetically noncollinear structure at a superconductor(S)/ ferromagnet(F) interface. In this context, the generation of triplet supercurrents through intrinsic ferromagnetic domain walls, which are naturally occurring noncollinear magnetic features, was proposed theoretically in the past decade. However, an experimental demonstration has been lacking in the literature, particularly because of the difficulty in accessing a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
3
19
0
Order By: Relevance
“…Regarding the effects of the domain structure, one should note that the presence of several ferromagnetic domains between the superconducting leads could generally give rise to essentially the same physics as in a JSV 63,64 . In particular, asymmetric non-Fraunhofer I c (B) patterns in SFS junctions with a complex multi-domain structure have been reported before 54,55 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effects of the domain structure, one should note that the presence of several ferromagnetic domains between the superconducting leads could generally give rise to essentially the same physics as in a JSV 63,64 . In particular, asymmetric non-Fraunhofer I c (B) patterns in SFS junctions with a complex multi-domain structure have been reported before 54,55 .…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 However, the experimental evidence to verify such models remains scarce. 31 In other recent developments, it was suggested that theoretically spin mixing can also be achieved by spin–orbit coupling (SOC). 32 36 This led to researching long-range proximity effects with Josephson junctions containing heavy metal interlayers.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of the long-range triplet component of the superconducting pairing at noncollinear orientations of magnetization in ferromagnetic layered systems is extensively studied in the framework of magnetic Josephson junctions (MJJs) ([ 1 3 ] for early works, and [ 4 5 ] for very recent papers), and superconductive spin valves (SSVs) [ 6 9 ]. The key points of the underlying physics are non-uniform magnetic configurations in the system that mix singlet and triplet superconducting pairing channels.…”
Section: Introductionmentioning
confidence: 99%